Personal data management with the Databox: what’s inside the box? - Mortier, Richard; Zhao, Jianxin; Crowcroft, Jon; Qi Li, Liang Wang; Haddadi, Hamed; Amar, Yousef; Crabtree, Andy; Colley, James; Lodge, Tom; Brown, Anthony; McAuley, Derek; Greenhalgh, Chris (2016)
We are all increasingly the subjects of data collection and processing systems that use data generated both about and by us to provide and optimise a wide range of services. Means for others to collect and process data that concerns each of us – often referred to possessively as “your data” – are only increasing with the long-heralded advent of the In- ternet of Things just the latest example. As a result, means to enable personal data management is generally recognised as a pressing societal issue.